Structural evolution of tungsten surface exposed to sequential low-energy helium ion irradiation and transient heat loading. (August 2017) - Sinclair, G.; Tripathi, J.K.; Diwakar, P.K.; Wirtz, M.; Linke, J.; Hassanein, A.
Highlights: Surface melting and mass loss by ELM-like heat loading were measured on W fuzz. Both laser and electron beam loading were used to replicate type-I ELMs. Surface melting on fuzz samples is driven by the local conglomeration of W fibers. Increased penetration depth of electron beam reduces degree of surface melting. In situ mass loss measurements reveal exponential increase in particle ejection. Abstract: Structural damage due to high flux particle irradiation can result in significant changes to the thermal strength of the plasma facing component surface (PFC) during off-normal events in a tokamak. Low-energy He + ion irradiation of tungsten (W), which is currently the leading candidate material for future PFCs, can result in the development of a fiber form nanostructure, known as "fuzz". In the current study, mirror-finished W foils were exposed to 100 eV He + ion irradiation at a fluence of 2.6 × 10 24  ions m −2 and a temperature of 1200 K. Then, samples were exposed to two different types of pulsed heat loading meant to replicate type-I edge-localized mode (ELM) heating at varying energy densities and base temperatures. Millisecond (ms) laser exposure done at 1200 K revealed a reduction in fuzz density with increasing energy density due to the conglomeration and local melting of W fibers. At higher energy densities (∼ 1.5 MJ m −2 ), RT exposures resulted in surface cracking, while 1200 K exposures resulted in surface roughening, demonstrating the role of base temperature on the crack formation in W. Electron beam heating presented similar trends in surface morphology evolution; a higher penetration depth led to reduced melt motion and plasticity. In situ mass loss measurements obtained via a quartz crystal microbalance (QCM) found an exponential increase in particle emission for RT exposures, while the prevalence of melting from 1200 K exposures yielded no observable trend.